2015
DOI: 10.1080/15289168.2015.1014991
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Psychoanalytic Psychotherapy and Behavioral Therapy Treatment in Children with Attention Deficit Hyperactivity Disorder and Oppositional Defiant Disorder

Abstract: The study compares the effectiveness of long-term psychoanalytic psychotherapy without medication with behavioral therapy and/or medication treatment. Seventy-three children with attention-deficit hyperactivity disorder (ADHD) and oppositional defiant disorder (ODD) participated in a controlled trial. The primary outcome was symptom reduction 38 months after the pre-treatment assessment. Secondary outcomes were significantly lower scores for Conners Parent and Teacher Rating Scale, Child Behavior Checklist and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 27 publications
0
16
0
1
Order By: Relevance
“…behavior disorders. 73 participants, aged 6-11 years old, with oppositional defiant disorder and/or attention deficit hyperactivity disorder were recruited into this controlled observational study (Laezer, 2015).…”
Section: Disruptive Behavior Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…behavior disorders. 73 participants, aged 6-11 years old, with oppositional defiant disorder and/or attention deficit hyperactivity disorder were recruited into this controlled observational study (Laezer, 2015).…”
Section: Disruptive Behavior Disordersmentioning
confidence: 99%
“…Seven of the studies (30%) had an active comparison group, three of which were treatment as usual (Balottin et al, 2014;Rossouw & Fonagy, 2012;Salzer et al, 2013), while the other four compared psychoanalytic treatment to therapeutic approaches including cognitive-behavioural therapy, family therapy and psychosocial interventions (Goodyer et al, 2016;Kolaitis et al, 2014;Laezer, 2015;Ryynänen et al, 2015). Of the remaining studies, four (24%) had a passive comparison group as they had a waitlist control group (Edlund & Carlberg, 2016;Edlund et al, 2014;Göttken et al, 2014;Weitkamp et al, 2014), while two (12%) used a community comparison group (Atzil-Slonim et al, 2011 and five (29%) had no control group or did not report outcomes of the control group (Clausen et al, 2012;Emanuel et al, 2014;Gatta et al, 2016;Krischer et al, 2013;Milrod et al, 2013;Salzer et al, 2014;Seiffge-Krenke & Nitzko, 2011;Stefini et al, 2013;Sugar & Berkovitz, 2011a, 2011b.…”
Section: Assessment Of Study Qualitymentioning
confidence: 99%
“…Although disruptive disorders are a common reason for referral to child mental health services, only six studies have specifically examined the efficacy of psychodynamic psychotherapy for these children. Three of these involve a mixed population including children diagnosed with Oppositional Defiant Disorder (ODD), Disruptive Disorder, Conduct Disorder (CD) and Attention Deficit Hyperactivity Disorder (ADHD) (Eresund, 2007 ; Laezer, 2015 ; Weitkamp et al, 2017 ). One study focused on children and young people specifically diagnosed with CD (Edginton et al, 2018 ), and one focused on children diagnosed with ODD (Prout et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…The findings showed that 31% of the children in the treatment group experienced clinically significant improvement compared with 8% of those in the control group. Laezer ( 2015 ) conducted a controlled observation study involving 73 children aged 6–11, with ODD or ADHD (which DSM-5 categorizes as a neurodevelopmental disorder). One group of participants received psychoanalytic psychotherapy, whilst the other group received behavioral therapy and/or medication.…”
Section: Resultsmentioning
confidence: 99%
“…​​​​ The NIMH Collaborative Multisite Multimodal Treatment Study of Children with Attention-Deficit/Hyperactivity Disorder, also known as the MTA study, (Arnold et al, 1997; Swanson et al, 2008) did not include it in the treatment arsenal, and neither the reviews of psychosocial treatments by Eyberg, Nelson and Boggs ( 2008​​​​) nor by Pelham and Fabiano (2008) comprised it. I only know of one systematic study of psychoanalytic therapy (Laezer, 2015). In this Frankfurt study, which was a controlled trial with a naturalistic observational design, 43 children received two years of psychotherapy without medication.…”
Section: Adhd and Psychodynamic Therapymentioning
confidence: 99%